UPAYA KOMISI PEMILIHAN UMUM (KPU) KOTA PEKANBARU DALAM PEMENUHAN HAK POLITIK PENYANDANG DISABILITAS PADA PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA PEKANBARU TAHUN 2017 - Lestari, Dina; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Every citizen has the right to be actively involved in political life. Similarly, with persons with disabilities as part of Indonesian citizens, persons with disabilities are also entitled to be actively involved in political life. Persons with disabilities are entitled to equal opportunities in Indonesian politics without discrimination. The formulation of the problem in this research: how the efforts of General Election Commission (KPU) Pekanbaru City in fulfilling the political rights of PwDs in the Election of Mayor and Vice Mayor of Pekanbaru Year 2017. This study aims to describe the efforts of the General Elections Commission (KPU) Pekanbaru in fulfillment political rights of persons on the Mayor and Vice Mayor of Pekanbaru City in 2017. This research uses a qualitative approach intended to understand the phenomenon of what is experienced by the subject of research holistically by way of description in the form of words and language in a natural context by utilizing various scientific methods . The type of research is descriptive type of research used to analyze data by describing or describing the data that has been collected as it is without intending to make conclusions that apply to the public.The results showed that the efforts made by the General Elections Commission (KPU) Pekanbaru City in the fulfillment of the political rights of people with disability has not been maximized. Efforts to fulfill the political rights of people with disabilities in the Mayor and Vice Mayor Election Pekanbaru in 2017 only focus on efforts to fulfill the right to vote. Persons with disabilities are only involved at the time of election (pencoblosaan) just as a voter. Efforts to fulfill accessibility, facilities and infrastructure election conducted by the General Election Commission (KPU) Pekanbaru City is also still very limited. Facilities and infrastructure provided only in the form of tool coblos (template braille) for the blind and visual interpreters for deaf people at the time of socialization. Special political socialization of persons with disabilities is only done once.Keywords: Pekanbaru Election Commission (KPU), Political Rights of Persons with Disabilities